Neurofibromatosis type 1 (NF1) and Associated Tumors - Rosenbaum, T.; Wimmer, K. (Klinische Pädiatrie, 2014)
Neurofibromatosis type 1 (NF1) is a frequent neurocutaneous syndrome that predisposes for various benign and malignant tumors. Most characteristic are neurofibromas which occur in almost all NF1 patients at some point in lifetime. Although neurofibromas are benign tumors they can be disfiguring and plexiform neurofibromas may progress to malignant peripheral nerve sheath tumors. Overall survival rates of patients with these malignant tumors are poor. Other neoplasias frequently observed in NF1 patients are pilocytic astrocytomas, gastrointestinal stromal tumors, pheochromocytomas and juvenile myelomonocytic leukemia. Several other tumors have been reported in NF1 patients but it is unclear if there is a true association between the particular tumor type and NF1. Some of these tumors might be caused by a rare recessively inherited childhood cancer syndrome termed constitutive mismatch repair deficiency syndrome which shows certain phenotypic overlap with NF1 but includes a broad spectrum of tumors which usually do not occur in NF1. The development of NF1-associated tumors is largely explained by the underlying defect of the NF1 gene which results in activation of the RAS proto-oncogene- a key mechanism of tumorigenesis. Several downstream effectors of activated RAS as well as cooperating molecular pathways have been identified. These insights provide the basis to develop novel targeted treatment strategies which are urgently needed to improve the outcome for patients with NF1-associated malignancies.
Keywords: neurofibromatosis type 1; constitutive mismatch repair deficiency syndrome; neurofibroma; optical pathway glioma; juvenile myelomonocytic leukemia